A bibliometric analysis of autism research in the field of education in Ibero-America: A WOS perspective: - Núñez Núñez, Teresa; Calvo Alvarez, María Isabel; González Santamaría, Virginia; Rondón Mejías, Bárbara; Hernandez Gonzalez, Osvaldo (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Education is a key tool for promoting the personal and socioemotional development of individuals with autism. However, to date, no bibliometric analysis has been conducted on this topic in the Ibero-American context. Aim. The purpose of this study was to analyze the annual production of original articles, productive journals, funding agencies, authors, research trends, and the most influential articles in the field of education and autism. Method. The WoS database (Education & Educational Research, Psychology Educational, Education Special, Education Scientific Disciplines) was used, and a total of 352 documents were analyzed. Results. The results showed a growing trend in annual publications. Elsevier, Spain, the funding agency Spanish Government, author Lorenzo G, the journal Research in Autism Spectrum Disorders, and Spanish and Brazilian universities were the most productive contributors. The main research trends focused on educational intervention, special and/or inclusive education, intellectual disability, and technology. Conclusion. This work reflects a significant increase in scientific production in Ibero-America in the field of education and autism, which is evident in research topics related to various socialization areas such as school, technology, and family. However, further research and evidence collection in this direction are still needed, particularly in Latin American countries that are in the process of development.
Keywords: autism; education; bibliometric analysis